2022
DOI: 10.3390/ijms23105760
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Released from Stem Cells as a New Therapeutic Strategy for Primary and Secondary Glomerulonephritis

Abstract: Current treatment of primary and secondary glomerulopathies is hampered by many limits and a significant proportion of these disorders still evolves towards end-stage renal disease. A possible answer to this unmet challenge could be represented by therapies with stem cells, which include a variety of progenitor cell types derived from embryonic or adult tissues. Stem cell self-renewal and multi-lineage differentiation ability explain their potential to protect and regenerate injured cells, including kidney tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 207 publications
(218 reference statements)
0
4
0
Order By: Relevance
“…This is in line with previous findings, whereby EVs derived from BMSCs protected renal tubular epithelial cells from apoptosis in different mouse models of acute kidney injury through an RNA-based mechanism [ 55 , 56 ]. EVs derived from MSCs from different sources carry several important anti-apoptotic microRNAs (miRNAs) such as miR-21/-30/-125b/-130a/ 199a/-210/-223/-242 , or proteins, such as PCNA, BCL-XL and BCL-2 [ 57 , 58 ]. Moreover, several studies have investigated and reported on the functional proteins inside EVs by MS/MS proteomic analysis, highlighting the presence of proteins involved in proliferation, cell adhesion and other key signaling pathways [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous findings, whereby EVs derived from BMSCs protected renal tubular epithelial cells from apoptosis in different mouse models of acute kidney injury through an RNA-based mechanism [ 55 , 56 ]. EVs derived from MSCs from different sources carry several important anti-apoptotic microRNAs (miRNAs) such as miR-21/-30/-125b/-130a/ 199a/-210/-223/-242 , or proteins, such as PCNA, BCL-XL and BCL-2 [ 57 , 58 ]. Moreover, several studies have investigated and reported on the functional proteins inside EVs by MS/MS proteomic analysis, highlighting the presence of proteins involved in proliferation, cell adhesion and other key signaling pathways [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cell supplementation in azithromycin-induced rat nephropathy models maintains podocyte viability, reduces glomerular inflammation, and delay the progression of glomerular sclerosis (30). Stem cell therapy for podocytedamaged nephropathy still requires further research to progress from experimental models to clinical application (31). In addition, recent studies have shown that knock out the of the sphingoline kinase 2 (Sphk2) gene or using the highly selective Sphk2 inhibitor, SLM6031434, can upregulate WT1 expression in podocytes, protect against podocyte disease, and prevent proteinuria (32).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although stem cells play an immunomodulatory role and can regenerate injured tissues, they also carry a potential risk for dedifferentiation and tumorigenesis. Stem-cell-derived extracellular vesicles were shown to possess the same anti-inflammatory/immunomodulatory properties of MSC and to be able to modulate fibrosis, and delay tubular and glomerular damage, without the inherent risks [ 128 ]. There is still a paucity of clinical studies about the role of EVs in KD.…”
Section: Extracellular Vesicles and Oxidative Stressmentioning
confidence: 99%